Evaluating the Comprehensive Development Framework : Ownership and Participation - Handoussa, Heba; Lancaster, Carol (World Bank, Washington, DC, 2016)
Country ownership is the linchpin of the Comprehensive Development Framework (CDF), according to a recent World Bank report on the CDF. This evaluation of the role of ownership and participation in the CDF will examine these issues by addressing five specific questions: (1) has the CDF been successful in reflecting the new development consensus, in particular, the emphasis on ownership and participation?; (2) to what extent have aid agencies and organizations adopted ownership and participation as central to their operations?; (3) has the existence of the Comprehensive Development Framework led to the emphasis on ownership and participation among aid agencies?; (4) to what extent have governments receiving aid ‘owned’ the aid and sought the participation of their bureaucracies, parliaments and civil societies in planning and implementing the aid-funded activities?; (5) has better ownership led to better-designed and implemented policies and fewer policy rollbacks?; The following sections will first introduce the concept of ownership and participation and their incorporation in the CDF; then examine the role of ownership and participation in the activities of aid donors; third, examine ownership and participation in the work of aid recipients and finally, the extent to which the CDF has been put into use and has helped internalize/operationalize the concept of ownership and participation.